Neonatal Hypertension: An Underdiagnosed Condition, A Review Article - Sharma, Deepak; Pandita, Aakash; Shastri, Sweta (Current Hypertension Reviews, 2014)
Advances in neonatology and intensive monitoring has increased our ability to identify and measure blood pressure in sick premature and term infants and this has contributed to an increased awareness of hypertension in the NICU. A few recent studies done by Zubrow and others have offered many new information on blood pressure values over the first month after birth and on other many intrinsic and extrinsic factors that can cause effects on the blood pressure in the neonatal period. There are no definite cut off for labelling hypertension in newborn period and also doubts are there on the pharmacological treatment. This is a field in neonatology which is least studied hence requires further inquiry. This review article will cover several aspects of neonatal hypertension like definition, normotensive data, etiology, clinical characteristics, diagnostic modalities, treatment choices and long term effect of these newborns.
Keywords: Calcium channel blocker